Analysis of Paudyal’s “The Parrot in the Cage” and Sama’s “Don’t Cut down the Trees, Brother Woodcutter” from Ecological Perspectives - Gurung, Raj Kumar (Literary Studies, 2024)
This paper analyzes the ecological reading of Paudyal’s “The Parrot in the Cage” and Sama’s “Don’t Cut down the Trees, Brother Woodcutter.” There are several factors of modernization responsible for the destruction of natural phenomena. The deterioration of flora and fauna has not been controlled though several government monitoring agencies have been actively working. There are limited research works on Nepali writers’ works regarding environmental issues. This study explores these two authors’ works to show how the deforestation and destruction of the wild lives take place. The findings of the study show that people are cutting down trees; hunters are hunting birds and animals; and the government is cutting down trees for constructing roads, airports, and city planning. Because of these causes, the ozone layer has been depleted; global warming has increased and people are suffering from skin cataracts; eye cataracts, and respiratory problems. The over-superiority complex of man has helped destroy the flora and fauna. Whatever change takes place in nature is irreversible. The study adopts the deep ecology theory that was propounded by Norwegian philosopher Arne Naess. This essay explains the causes and effects of deforestation. The study also analyses the related consequences of deforestation. This is explanatory research rather than exploratory. The main purpose of this paper is to minimize ecological degradation and environmental problems. The study also attempts to find necessary solutions like afforestation, reforestation, and alternative energy.